Partisipasi Politik Perempuan dalam Partai Keadilan Sejahtera (PKS) di Kabupaten Jepara - Haryati, Eri; ., Yuwanto; ., Fitriyah (Journal of Politic and Government Studies, 2017)
Abstract. Gender equation concept has been spread out and developing in such way that affecting the reformation of Indonesia. One the changes that did by the reformation related to the system which aim to make women can fight for her interests in many sector, and politic is one of them. Political party is one of the most important factor that deciding whether the women’s political participation and representation. Women’s political participation will never fully happen if the political party does not have the commitment to support it.The research discussed a woman political participation practiced on Partai Keadilan Sejahtera, Moslem Welfare Justice Party. Research method that used is the qualitative approach by collecting data using deep interview, observation, and document study. Informant of this study are Head of DPD Partai Keadilan Sejahtera (PKS) Kabupaten Jepara, Staff of DPD) Partai Keadilan Sejahtera (PKS) Kabupaten Jepara, and Head of BPKK DPD Partai Keadilan Sejahtera (PKS) Kabupaten Jepara.Result of this study shows that women’s political participation in PKS Kabupaten Jepara is good, although there are still has some obstacles. The biggest obstacle comes from within women cadres. They are not enthusiastic about competing with man cadres because they think an intense competition will take up much of their time. Women claim they have difficulties to split their time for household duties, professional duties and also the duties that connected to their position in the political party. In the end, women prioritizing household duties rather than other duties. As a result, women become more comfortable with their position as good supporters of PKS and not as competitors for men in obtaining certain positions. Most of the affairs that are not related to womanhood are entirely handed over to male cadres.